Determining the frequency of burn wound dressing for clinically competent nursing students: establishing standards based on learning curves - Batoul Alizadeh-Taghiabad; Seyyed Reza Mazloum; Kheizaran Miri; Mohammad Namazinia (BMC Medical Education, 2023)
Abstract Background The primary objective of clinical practice in nursing education is to achieve mastery of clinical skills through repetitive practice. Therefore, there exists a correlation between the frequency of skill demonstration and clinical competency. This study aimed to address the following question: How many times should a nursing student perform burn wound dressing to attain clinical competency? Methods This time series study was conducted on 41 junior nursing students who were selected through a census sampling method at Neyshabur School of Nursing from spring 2015 to summer 2021. The data collection tool was a researcher-made competency evaluation checklist (CEV). The competency score of each student for each skill demonstraion episode was evaluated using the Competency Evaluation Checklist (CEV) and recorded on the learning curve until a plateau was reached. SPSS16 and repeated measures analysis of variance (ANOVA) were used. Results The mean competency score of burn wound dressing was 67.5 ± 11.0 (out of 100) during the first attempt, which increased to 95.9 ± 4.3 by the ninth attempt. The learning curve for the burn wound dressing skill reached a plateau after five attempts. Additionally, by the fifth attempt of dressing the burn wound, all students could accurately identify the depth, extent, and severity of the wound. Conclusions Establishing a standardized frequency for clinical skill performance and ensuring ample practice opportunities can have significant benefits in nursing education systems. These benefits include long-lasting learning, reduced costs, and improved effectiveness. As a result, nurse managers and lecturers should consider the resources available in their educational systems and strive to provide students with adequate opportunities and a supportive environment to practice their skills.